Oral treatment with a zinc complex of acetylsalicylic acid prevents diabetic cardiomyopathy in a rat model of type-2 diabetes: activation of the Akt pathway. Issue 1 (December 2016) - Korkmaz-Icöz, Sevil; Al Said, Samer; Radovits, Tamás; Li, Shiliang; Brune, Maik; Hegedűs, Péter; Atmanli, Ayhan; Ruppert, Mihály; Brlecic, Paige; Lehmann, Lorenz; Lahrmann, Bernd; Grabe, Niels; et al.
Abstract Background Type-2 diabetics have an increased risk of cardiomyopathy, and heart failure is a major cause of death among these patients. Growing evidence indicates that proinflammatory cytokines may induce the development of insulin resistance, and that anti-inflammatory medications may reverse this process. We investigated the effects of the oral administration of zinc and acetylsalicylic acid, in the form of bis(aspirinato)zinc(II)-complex Zn(ASA)2, on different aspects of cardiac damage in Zucker diabetic fatty (ZDF) rats, an experimental model of type-2 diabetic cardiomyopathy. Methods Nondiabetic control (ZL) and ZDF rats were treated orally with vehicle or Zn(ASA)2 for 24 days. At the age of 29–30 weeks, the electrical activities, left-ventricular functional parameters and left-ventricular wall thicknesses were assessed. Nitrotyrosine immunohistochemistry, TUNEL-assay, and hematoxylin-eosin staining were performed. The protein expression of the insulin-receptor and PI3K/AKT pathway were quantified by Western blot. Results Zn(ASA)2 -treatment significantly decreased plasma glucose concentration in ZDF rats (39.0 ± 3.6 vs 49.4 ± 2.8 mM, P < 0.05) while serum insulin-levels were similar among the groups. Data from cardiac catheterization showed that Zn(ASA)2 normalized the increased left-ventricular diastolic stiffness (end-diastolic pressure–volume relationship: 0.064 ± 0.008 vs 0.084 ± 0.014 mmHg/µl; end-diastolic pressure: 6.5 ± 0.6 vs 7.9 ± 0.7 mmHg, P < 0.05). Furthermore, ECG-recordings revealed a restoration of prolonged QT-intervals (63 ± 3 vs 83 ± 4 ms, P < 0.05) with Zn(ASA)2 . Left-ventricular wall thickness, assessed by echocardiography, did not differ among the groups. However histological examination revealed an increase in the cardiomyocytes' transverse cross-section area in ZDF compared to the ZL rats, which was significantly decreased after Zn(ASA)2 -treatment. Additionally, a significant fibrotic remodeling was observed in the diabetic rats compared to ZL rats, and Zn(ASA)2 -administered ZDF rats showed a similar collagen content as ZL animals. In diabetic hearts Zn(ASA)2 significantly decreased DNA-fragmentation, and nitro-oxidative stress, and up-regulated myocardial phosphorylated-AKT/AKT protein expression. Zn(ASA)2 reduced cardiomyocyte death in a cellular model of oxidative stress. Zn(ASA)2 had no effects on altered myocardial CD36, GLUT-4, and PI3K protein expression. Conclusions We demonstrated that treatment of type-2 diabetic rats with Zn(ASA)2 reduced plasma glucose-levels and prevented diabetic cardiomyopathy. The increased myocardial AKT activation could, in part, help to explain the cardioprotective effects of Zn(ASA)2 . The oral administration of Zn(ASA)2 may have therapeutic potential, aiming to prevent/treat cardiac complications in type-2 diabetic patients.